Swimming exercise and clove oil can improve memory by molecular responses modification and reduce dark cells in rat model of Alzheimer's disease - Z. Gorgin Karaji; M. Fathi; R. Mirnasori; E.A. van der Zee (Experimental Gerontology, 2023)
Alzheimer's disease (AD) is marked by reduced acetylcholine receptor (AChR) density and an increase in nucleotide oligomerization domain (NOD)-like receptors NLR family, pyrin domain containing 1 (NLRP1). We examined the effect of swimming and consumption of clove supplements on memory, dark cells, and α7nAChR and NLRP1 mRNA and protein expression in the hippocampus of the rat model of AD. Forty-eight rats were divided into six groups: sham (sh), healthy-control (HC), Alzheimer (-control (AC), -training (AT), -training-supplement (ATS), and -supplement (AS)). Alzheimer was induced by injection of amyloid β1–42 (Aβ1–42). Swimming exercise protocol (30 min) and gavaging clove supplement (0.1 mg/kg) were administered daily for three weeks. The results indicated that in response to AD, α7 nicotinic acetylcholine receptor (α7nAChR) mRNA and protein rate (p = 0.001) and memory (p = 0.003) were significantly decreased. In contrast, NLRP1 mRNA and protein rate (p = 0.001) and dark cells (p = 0.001) were significantly increased. This is while exercise and clove supplementation improved Alzheimer-induced changes in α7nAChR, NLRP1, memory, and dark cells (p < 0/05). The present study indicated that exercising and consuming clove supplementation could improve memory by increasing α7nAChR and decreasing NLRP1 and dark cells.